Reliability and Validity of a Korean Version of the Tinnitus Primary Function Questionnaire - Shin, Jinbae; Heo, Sohee; Lee, Ho-Ki; Tyler, Richard; Jin, In-Ki (American journal of audiology, 2019)
Purpose The aim of this study was to evaluate the reliability and validity of a Korean version of the Tinnitus Primary Function Questionnaire (K-TPFQ). Method A total of 79 subjects participated in the study. All participants completed the K-TPFQ, and the Korean versions of the Pittsburgh Sleep Quality Index ( Buysse, Reynolds, Monk, Berman, & Kupfer, 1989 ; Sohn, Kim, Lee, & Cho, 2012 ), the Beck Depression Inventory ( Beck, Ward, Mendelson, Mock, & Erbaugh, 1961 ; Jo, Park, Jo, Ryu, & Han, 2007 ), the State-Trait Anxiety Inventory questionnaire ( Cho & Choi, 1989 ; Spielberger & Gorsuch, 1983 ), and the Tinnitus Handicap Questionnaire ( Kuk, Tyler, Russell, & Jordan, 1990 ). Results The K-TPFQ exhibited good or high internal consistency and reliability (Cronbach's alpha range: .91-.95, item-total correlation range: .50-.82). The total score derived from the items of the K-TPFQ and its subcategories was moderately correlated with that of questionnaires that measure similar parameters (Pearson correlation coefficient range: .50-.79). Conclusions Overall, the results of this study indicate that the K-TPFQ is reliable and valid. Therefore, the current translated version of the K-TPFQ is applicable to subjects with Korean as their 1st language and proves to be a useful tinnitus questionnaire.